Experiments and numerical simulations on hovering three-dimensional flexible flapping wings. (1st November 2022) - Diaz-Arriba, D; Jardin, T; Gourdain, N; Pons, F; David, L
Abstract: In this paper, the applicability and accuracy of high-fidelity experimental and numerical approaches in the analysis of three-dimensional flapping (revolving and pitching) wings operating under hovering flight conditions, i.e. where unsteady and three-dimensional rotational effects are strong, are assessed. Numerical simulations are then used to explore the role of mass and frequency ratios on aerodynamic performance, wing dynamics and flow physics. It is shown that time-averaged lift increases with frequency ratio, up to a certain limit that depends on mass ratio and beyond which upward wing bending and flexibility induced phase lag between revolving an pitching motions at stroke reversal become strong and contribute to phases of negative lift that counterbalances the initial lift increase. This wing dynamics, which is dominated by spanwise bending, also affects wing–wake interactions and, in turn, leading edge vortex formation.